PROBLEM ANALYSIS OF PRISONER’S ASSAULTS ON PRISON GUARDS ON DUTY IN POLAND BETWEEN 2013-2017 - ŁUSZCZ Paweł (2018)
It should be said that this analysis covered the period of over 5 years from August 2013 to the end of 2017. The most vulnerable officers at the risk of assault are officers of the security department and the least officers of the quartermaster department. If we analyze the aggression of the prisoners themselves and their actions, the most common event is: A hand hit − and here you can see a large increase from 22 such acts in 2014 to 39 in 2017. Therefore, it seems reasonable that the managers of penitentiary units − directors − should make efforts and direct the largest number of officers to serve in residential wards. To increase the number of security officers. The task of the head of the security department is, therefore, to depersonalize people and divide responsibilities so that they insure themselves properly during the performance of their official tasks. Training should be provided to the officers in the scope of the exhibition procedure − incarceration by the detainee. It can therefore be said that using the presented analysis as well as the proposed conclusions during the organization of the service for officers − we will provide them with greater security as well as comfort of work.